MicroRNA profile before and after antiviral therapy in liver transplant recipients for hepatitis C virus cirrhosis. Issue 1 (January 2014) - Gelley, Fanni; Zadori, Gergely; Nemes, Balazs; Fassan, Matteo; Lendvai, Gabor; Sarvary, Eniko; Doros, Attila; Gerlei, Zsuzsanna; Nagy, Peter; Schaff, Zsuzsa; Kiss, Andras
Abstract Background and Aim Management of hepatitis C virus (HCV) recurrence is a major challenge after liver transplantation. Significant dysregulated expression of HCV receptors (i.e. claudin‐1, occludin, tetraspanin CD81, scavenger receptor type B1) has been shown recently during HCV infection. This might facilitate hepatocytic entry and reinfection of HCV. MicroRNAs (miRs) play role in the regulation of gene expression. We aimed to characterize miR expression profiles related to HCV infection and antiviral therapy in adult liver transplant recipients, with special emphasis on miRs predicted to target HCV receptors. Methods Twenty‐eight adult liver transplant recipients were enrolled in the study. Paired biopsies were obtained at the time of HCV recurrence and at the end of antiviral treatment. MiRs for HCV receptors were selected using target prediction software. Expression levels of miR‐21, miR‐23a miR‐34a, miR‐96, miR‐99a*, miR‐122, miR‐125b, miR‐181a‐2*, miR‐194, miR‐195, miR‐217, miR‐221, and miR‐224 were determined by reverse transcription–quantitative polymerase chain reaction. Results miR‐99a* and miR‐224 expressions were increased in HCV recurrence samples, while miR‐21 and miR‐194 were decreased in comparison to normal liver tissue. Increased expressions of miR‐221, miR‐224, and miR‐217 were observed in samples taken after antiviral therapy when compared with HCV recurrence samples. High HCV titer at recurrence was associated with higher level of miR‐122. Conclusions Samples at recurrence of HCV and after antiviral therapy revealed distinct HCV‐related miR expression profiles, with significant dysregulation of those miRNAs potentially targeting mRNAs of HCV receptors. In particular, miR‐194 and miR‐21 might be involved in the regulation of HCV receptor proteins' expression during HCV infection and antiviral therapy.